Trends and Treatment of Sub-Acute Sclerosing Panencephalitis: An Updated Review. (December 2021) - Memon, Shahzeb Ali; Afzal, Syed Shabbir; Tukruna, Alaa; Khan, Asma Tasnim; Tebha, Sameer Saleem; Zaidi, Zain Ali
Measles infection, caused by the "Rubeola" virus is a highly contagious disease with outrageously fatal consequences. Initiating with a variety of symptoms including fever, cough, conjunctivitis, and runny nose, it can lead to more severe sequelae including sub-acute sclerosing pan-encephalitis which is a potentially fatal and serious complication of measles. The lackluster vaccination processes in underdeveloped areas of the world due to suboptimal immunization programs, scarce resources, and insufficient political constancy still leads to increased cases of measles and its complications. A variety of management programs including the use of several medications have been introduced according to the literature in order to counter this dreadful disease. In this review article, we focus on assessment of the previous literature and discussing the possible treatment modalities of this currently irremediable disease.